Drawing to an inside straight the legacy of an absent father - Varon, Jodi, 1953- (University of Missouri Press, 2006)
"Varon interweaves recollections of growing up in Vietnam-era Denver with stories of her gambler father, son of Sephardic Jewish immigrants, and offers an introduction to Sephardic culture contrasted with Ashkenazic culture, examines the forging of identity within the potentially destructive American "melting pot," and challenges stereotypes of the American West"--Provided by publisher.